Hepatitis B virus-associated B-cell non-Hodgkin lymphoma in non-endemic areas in Western Europe: Clinical characteristics and prognosis. Issue 2 (February 2020) - Lemaitre, Marine; Brice, Pauline; Frigeni, Marco; Hermine, Olivier; Arcaini, Luca; Thieblemont, Catherine; Besson, Caroline
Abstract : The association between B-cell non-Hodgkin lymphoma (NHL) and hepatitis B virus (HBV) is well demonstrated by epidemiological studies. Most studies concerning this association have been conducted in endemic areas. Thus, little is known concerning the clinical characteristics of HBV-related lymphomas in non-endemic areas. Here, we report the characteristics and outcomes of 39 patients with active HBV infection and B-cell NHL collected retrospectively in France and Italy. We also compared their characteristics with those of HCV-positive patients with NHL. The gender ratio (M/F) was 3.3 and the median age at NHL diagnosis, 59 years. The pathological distribution was 24 (62%) diffuse large B-cell lymphomas (DLBCLs) and 15 (38%) other lymphomas subtypes: marginal zone lymphoma ( n  = 6), follicular lymphoma ( n  = 3), mantle cell lymphoma ( n  = 2), Burkitt's lymphoma ( n  = 1), and not otherwise specified low-grade B-NHL ( n  = 3). Treatment included antiviral therapy for 35 patients (90%). Twenty-two (92%) DLBCL patients received an R-CHOP or R-CHOP-like regimen, leading to complete remission for 18 (75%).At one year, 21 DLBCL patients (88%) were alive, and 13 other B-cell lymphoma patients (87%) were alive. This European study underscores the predominance of DLBCL among patients with active HBV infection and their similar outcomes to non-HBV infected patients with DLBCL when treated with R-CHOP and antivirals.